Working in sport and recreation a practical approach - Saipe, Rob (Stanley Thornes (Publishers), 1999)
Rob Saipe's comprehensive text is for all those studying sport and recreation, or working in this expanding industry. Focusing on the requirements of the key courses in the area, the book covers all aspects of operational services and coaching.